Feed Intake and Growth Performance of Native Ducks (Anas platyrhynchos domesticus) Fed Mung Bean (Vigna radiata) Sprouts - Mercury A. del Rosario; Sance J. Secondez (Journal of Global Innovations in Agricultural Sciences, 2025)
In regions like the Philippines, where climatic unpredictability can substantially affect forage production, ensuring an efficient and reliable feed source is of utmost importance. This study investigates the utilization of Mung Bean (Vigna radiata) Sprout as a potential feed ingredient for native ducks (Anas platyrhynchos domesticus) and its effect on feed intake and growth performance. Although Mung Bean Sprout is not a traditional feed preservation strategy, it could help stabilize poultry nutrition. A total of twenty-five female ducks were randomly assigned to individual cages to prevent cross-contamination, adhering to strict hygiene practices. A Completely Randomized Design (CRD) was implemented with five treatments and five replicates. The treatments included various proportions of Mung Bean Sprout and commercial feed. While there were no significant differences (p < 0.05) in feed intake among treatments, ducks fed with 50% MBS + 50% commercial feed (T2) exhibited the highest growth rates and improved feed conversion efficiency compared to other treatments. These findings underscore the potential of Mung Bean Sprout as a valuable feed ingredient for improving the growth performance of native ducks, particularly in regions with volatile forage production due to climatic variability. This research sheds light on a promising avenue for sustainable poultry nutrition in the face of climate-related challenges. Keywords: Food security, climate impact, dietary supplementation, feed efficiency, growth performance, carcass quality.